1968
DOI: 10.1677/joe.0.0410263
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of [4-14c]norethisterone in Women

Abstract: After the administration of norethisterone to seven human subjects 37\m=.\4 % to 80\m=.\6 % of the dose was excreted in the urine within 5 days. About half of the urinary radioactivity was extractable after acid or enzymatic hydrolysis and about 80 % was extracted by using a serial hydrolytic and extraction procedure. About 15 % of the urinary radioactivity was present as sulphate conjugates. About 5 % of the urinary radioactivity was present in acidic or phenolic compounds. No metabolism ofthe ethynyl group s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1968
1968
2000
2000

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(7 citation statements)
references
References 14 publications
(21 reference statements)
1
6
0
Order By: Relevance
“…All the compounds tested had a 17,/-OH. This group is not oxidized when there is a 17a-ethinyl group, and the latter has been shown to be very resistant to metabolism (Fotherby, Kamyab, Littleton & Klopper, 1966;Kamyab, Fotherby & Steele, 1969;Williams, Nilsen & Blahey, 1967). Our studies emphasize the importance of 17a-ethinyl substitution but leave open the question whether 3-hydroxyl, aromatic A ring and 17f/-OH are necessary for inhibition of bile secretion.…”
Section: Discussionmentioning
confidence: 64%
“…All the compounds tested had a 17,/-OH. This group is not oxidized when there is a 17a-ethinyl group, and the latter has been shown to be very resistant to metabolism (Fotherby, Kamyab, Littleton & Klopper, 1966;Kamyab, Fotherby & Steele, 1969;Williams, Nilsen & Blahey, 1967). Our studies emphasize the importance of 17a-ethinyl substitution but leave open the question whether 3-hydroxyl, aromatic A ring and 17f/-OH are necessary for inhibition of bile secretion.…”
Section: Discussionmentioning
confidence: 64%
“…Subject M 3 received 1 pc [14C]norgestrel adsorbed on to lactose in a gelatine capsule orally. The details of the investiga¬ tions together with the methods used for the estimation of radioactivity in urine and blood have been described previously (Kamyab, Littleton & Fotherby, 1967;Kamyab, Fotherby & Klopper, 1968a). For the isolation and identification of norgestrel metabolites, urine from subject M 2 was pooled and extracted in 11. quantities.…”
Section: Methodsmentioning
confidence: 99%
“…DISCUSSION Norgestrel (18-methylnorethisterone) and lynestrenol (3-deoxynorethisterone) are both chemically related to norethisterone (17a-ethynyl-19-nortestosterone), but these three synthetic progestins show marked differences in biological activity. Since the methods used in the present study of the metabolism of norgestrel are similar to those used previously for lynestrenol (Kamyab, Fotherby & Klopper, 1968&) and nore¬ thisterone (Kamyab et al 1968a) it is possible to compare the metabolism of the three compounds. The recovery of radioactivity in urine after the injection of norgestrel (40%) was similar to that obtained with lynestrenol (43-7%) but less than that obtained with norethisterone (53-9%).…”
Section: Radioactivity In Urine and Bloodmentioning
confidence: 99%
“…Since these investigations were carried out on the day on which the women were subjected to laparotomy, a 24 h sample of urine was collected starting at the time of injection of the dose, and blood samples were taken 1, 3 and 24 h after admini¬ stration of the dose in order to see whether there was any difference in these values from those obtained in normal subjects not subjected to an operation (Kamyab, Fotherby & Klopper, 1968). The mean values for the amount of administered dose recovered in urine and for the extraction of radioactivity from urine are compared in Table 7 with values obtained in normal subjects.…”
Section: Radioactivity In Urine and Bloodmentioning
confidence: 99%
“…These values are similar to those obtained previously in normal subjects and suggest that no major change in the metabolism of norethisterone occurred in the patients during the pre-operative period. DISCUSSION Although the metabolism of norethisterone in vivo has been investigated in man by Layne, Golab, Arai & Pincus (1963), Murata (1967), Kamyab et al (1968) and Gerhards, Hecker, Hitze, Nieuweboer & Bellmann (1971), no study of the localization of this synthetic progestogen in human tissues has been reported. The present investigation shows that norethisterone passes into adipose tissue and all the tissues of the reproductive tract within 1 h of injection, reaching particularly high con¬ centrations in endometrium and stroma.…”
Section: Radioactivity In Urine and Bloodmentioning
confidence: 99%